Langmuir Films of Poly(-Toluidine) and Poly(-Methoxyaniline) at the Water–Air Interface - Iryna Opaynych; A. Ukrainets; O. Aksimentyeva (Adsorption Science & Technology, 2007)
The behaviour of monomolecular layers prepared on a liquid surface may be considered as a limiting case of adsorption. In the present work, measurements of surface-pressure isotherms have been used to examine the effect of the solvent (tetrahydrofuran, chloroform) and polymer concentration on the formation of poly( o -toluidine) (PoTl) and poly( o -methoxyaniline) (PoMA) monolayers at the water surface. The PoTl monolayer exhibited a hysteresis loop when the PoMA and PoTl monolayers were studied under compression/expansion conditions. In contrast, the mobility of the monomer units in the PoMA films formed at the water surface enabled them to rapidly restore their structure.